Nekatolíci v Růžové na Děčínsku na cestě mezi herrnhutskou a evangelickou církví (1840-1875) - Zeman, Václav (Lidé města, 2009)
A debate society in Růžová (Rosendorf in German) in Northern Bohemia, active in the 1830’s, began to show tendencies for reading religious texts coming from the milieu of the Moravian Brethren Church in Herrnhut. Several men from Růžová had taken part of religious services in Herrnhut. However, these non-Catholics were exposed by the Catholic authorities. Nevertheless, they remained in the church until 1860. Similar phenomena also occurred in a few close villages. For twenty years, non-Catholic meetings took place that the Catholic authorities unsuccessfully tried to stop. In 1860-1861 several dozens converted to the Lutheran Church, since the Moravian Brethren Church was not permitted in the country. A church was built in Růžová. A pastor of the Moravian Brethren Church worked there until 1876. In 1875, Růžová was promoted to a parish of the Lutheran Church and, together with the departure of the pastor from Moravian Brethren Church, this step meant a complete integration into the structures of the Lutheran Church and also failure in missionary effort of Moravian Church in this region.